Teaching History With Custom-Built Board Games. (April 2018) - Hoy, Benjamin
Purpose. This article investigated the potential of acustom-built board game as a means to teachhistorical empathy, improve classparticipation, and to improvestudent understanding of the limitations of archival collections. Method. Participant behavior as well as verbal and written feedback were collected during a pilot study of POLICING THE SOUND. A total of 88undergraduate andgraduate participants from History and Indigenous Studies took part during the pilot study. Results. Student participation and understanding of historical context improved during the game. While graduate and undergraduate students showed similarity in theirenjoyment of the game and their belief that it made historical arguments, thecurricular differences in graduate and undergraduate programs influenced how each group approached the game. Conclusion. Participant feedback, facilitator observation, and external observation indicate that groups of players can resolve confusion more efficiently than individual players can, time constrained decision-making may help maintain student engagement, an inability to win does not necessarily cause disengagement in short educational games, and that a structured debrief is important in achieving educational goals even in custom-built games.